107k views
5 votes
6 + 8(x - 1) = 2(3x + 4)

6 + 8x - 8 = 6x + 8
8x - 2 = 6x + 8
14x - 2 = 8
14x = 10
5
x=7
The mistake was.....
The correct answer is x=?

2 Answers

5 votes
The mistake was is he subtracted at the end instead of dividing, the answer is 5/7
User Phil Ringsmuth
by
4.8k points
4 votes

Explanation:

6+ 8x-8 = 6x +8

-2+8x= 6x+8

-6x+8x=2+8

2x=10/2

x=5

The mistake was that u didn't change 6x in ti-6x. when u transfer numbers over the = thery change if positive to negative and if negative to positive

I hope I helped

User Aaron Lockey
by
5.3k points